Changing associations of episiotomy and anal sphincter injury across risk strata: results of a population-based register study in Finland 2004–2011. Issue 8 (17th August 2013) - Räisänen, Sari; Cartwright, Rufus; Gissler, Mika; Kramer, Michael R; Laine, Katariina; Jouhki, Maija-Riitta; Heinonen, Seppo
Abstract : Objectives: To evaluate the changing association between lateral episiotomy and obstetric anal sphincter injury (OASIS) for women with low and high baseline risk of OASIS. Design: A population-based register study. Setting: Data gathered from the Finnish Medical Birth Register for the years 2004−2011. Participants: All women with spontaneous vaginal or vacuum-assisted singleton births in Finland (n=384 638). Main outcome measure: OASIS incidence. Results: During the study period, the incidence of OASIS increased from 1.3% to 1.7% in women with first vaginal births, including women admitted for first vaginal birth after a prior caesarean section and from 0.1% to 0.3% in women with at least one prior birth, whereas episiotomy rates declined from 56.7% to 45.5% and 10.1– 5.3%, respectively. At the study onset, when episiotomy was used more widely, it was negatively associated with OASIS in women with first vaginal births, but as episiotomy use declined it became positively associated with OASIS. Women with episiotomy were complicated by OASIS with clearly higher risk scores than women without episiotomy suggesting that episiotomy was clearly protective against OASIS. OASIS occurred with lower mean risk scores among women with and without episiotomy over time. However, OASIS incidences increased only among women with episiotomy, whereas it decreased or remained among women without episiotomy. Conclusions: The cross-over effect between episiotomy and OASIS could be explained by increasing disparity in baseline OASIS risk between treated and untreated women, since episiotomy use declined most in women at low OASIS risk. Episiotomy rate can be safely reduced in low-risk women but interestingly along with the policy change the practice to cut the episiotomy became less protective among high-risk women.